Peningkatan Aktivitas Afrodisiak Mikroemulsi Icariin, Ekstrak Purwaceng dan Ekstrak Pasak Bumi: Enhancement of Aphrodisiac Activity of Icariin, Purwaceng Extract, and Pasak Bumi Extract Microemulsion - Ajeng Puspo Aji; Rochany Septianingsih; Septiana Indratmoko; Y, Asep Nurrahman; Lisa Indriana (Jurnal Tumbuhan Obat Indonesia, 2024)
Erectile dysfunction (ED) refers to medical issues concerning men's sexual health. Purwaceng, pasak bumi, and epimedium plants contain aphrodisiac compounds that can boost stamina, libido (sexual desire), and male fertility. The formula for microemulsions is 80: PEG 400: oil shavings in a ratio of 73.6711: 12.5705: 13.7584, with icariin, purwaceng, and pasak bumi added. The microemulsion system was created because it contained a large number of active ingredients. The stability of a microemulsion is further influenced by surfactants (tween 80) and cosurfactants (PEG 400) as emulsifiers, as well as the oil used as a solvent for the active component (bottled oil). The goal of this study was to create a microemulsion that would mix icariin, pasak bumi, and purwaceng substances to improve solubility and synergize pharmacological effects. The formulation is optimized using Simplex Lattice Design (SLD) to produce the optimal formula. The microemulsion formulations of icariin, pasak bumi extract, and purwaceng extract produce optimal microemulsions and enter into good microemulsion susceptibility. They can also increase the aphrodisiac effectiveness when compared to the administration of the single active substance icariin, pasak bumi extract, and purwaceng extract. As a result, this product exhibits microemulsion capabilities, allowing it to minimize dose while increasing effect.